2018
DOI: 10.5530/ijopp.11.4.42
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Severity of Sickle Cell Disease in Amravati District of Maharashtra

Abstract: Objective: The present study was undertaken to determine the prevalence and severity of Sickle Cell Disease among carriers and sufferers belonging to Amravati district. Methodology: Screening camps were held in different regions from which only positive groups of sickle cell solubility were considered for prevalence. A patient interview form was prepared with informed consent. The questionnaire was prepared with a view to collect data on the disease status of the sufferers only. Results: It was found that over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…According to Table 1, the most common blood group present in βthalassemia patients was O (34.6%), followed by B (29%), and A (25%), while the least common blood group was AB (11.4%). The ABO blood group pattern observed in the current study was O>B>A>AB, which is similar to the past studies [14][15][16][17]. It was found that Rh factor was present in most of the β-thalassemia patients (94.2%) and absent only in a few (5.8%) patients.…”
Section: Discussionsupporting
confidence: 90%
“…According to Table 1, the most common blood group present in βthalassemia patients was O (34.6%), followed by B (29%), and A (25%), while the least common blood group was AB (11.4%). The ABO blood group pattern observed in the current study was O>B>A>AB, which is similar to the past studies [14][15][16][17]. It was found that Rh factor was present in most of the β-thalassemia patients (94.2%) and absent only in a few (5.8%) patients.…”
Section: Discussionsupporting
confidence: 90%